Dietary Phosphorus and Calcium Utilization in Growing Pigs: Requirements and Improvements - Lautrou, Marion; Narcy, Agnès; Dourmad, Jean-Yves; Pomar, Candido; Schmidely, Philippe; Létourneau Montminy, Marie-Pierre (Frontiers in Veterinary Science, 2021)
The sustainability of animal production relies on the judicious use of phosphorus (P). Phosphate, the mined source of agricultural phosphorus supplements, is a non-renewable resource, but phosphorus is essential for animal growth, health, and wellbeing. P must be provided by efficient and sustainable means that minimize the phosphorus footprint of livestock production, by developing precise assessment of the bioavailability of dietary P using robust models. About 60% of the phosphorus in an animal’s body occurs in bone at a fixed ratio with calcium (Ca) and the rest is found in muscle. The P and Ca requirements must be estimated together; they cannot be dissociated. While precise assessment of P and Ca requirements is important for animal wellbeing, it can also help to mitigate the environmental effects of pig farming. These strategies refer to multicriteria approaches of modeling, efficient use of the new generations of phytase, depletion and repletion strategies to prime the animal to be more efficient, and finally combining these strategies into a precision feeding model that provides daily tailored diets for individuals. The industry will need to use strategies such as these to ensure a sustainable plant-animal-soil system and an efficient P cycle.